The guests of god (Berkshire, Eng. : Meridian International Communications, 1991)
The video traces the steps of a European Muslim convert family from their home in Germany to the holy cities of Mecca and Medina.
DVD format
Title from container
Keywords: Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca; Muslim converts from Christianity